Gluten‐Free Precooked Rice‐Yellow Pea Pasta: Effect of Extrusion‐Cooking Conditions on Phenolic Acids Composition, Selected Properties and Microstructure. Issue 5 (13th April 2016) - Bouasla, Abdallah; Wójtowicz, Agnieszka; Zidoune, Mohammed Nasereddine; Olech, Marta; Nowak, Renata; Mitrus, Marcin; Oniszczuk, Anna
Abstract: Rice/yellow pea flour blend (2/1 ratio) was used to produce gluten‐free precooked pasta using a single‐screw modified extrusion‐cooker TS‐45. The effect of moisture content (28%, 30%, and 32%) and screw speed (60, 80, and 100 rpm) on some quality parameters was assessed. The phenolic acids profile and selected pasta properties were tested, like pasting properties, water absorption capacity, cooking loss, texture characteristics, microstructure, and sensory overall acceptability. Results indicated that dough moisture content influenced all tested quality parameters of precooked pasta except firmness. Screw speed showed an effect only on some quality parameters. The extrusion‐cooking process at 30% of dough moisture with 80 rpm is appropriate to obtain rice‐yellow pea precooked pasta with high content of phenolics and adequate quality. These pasta products exhibited firm texture, low stickiness, and regular and compact interne structure confirmed by high score in sensory overall acceptability.